Effects of GPR139 agonism on effort expenditure for food reward in rodent models: Evidence for pro-motivational actions. (1st August 2022) - Münster, Alexandra; Sommer, Susanne; Kúkeľová, Diana; Sigrist, Hannes; Koros, Eliza; Deiana, Serena; Klinder, Klaus; Baader-Pagler, Tamara; Mayer-Wrangowski, Svenja; Ferger, Boris; Bretschneider, Tom; Pryce, Christopher R.; et al.
Abstract: Apathy, deficiency of motivation including willingness to exert effort for reward, is a common symptom in many psychiatric and neurological disorders, including depression and schizophrenia. Despite improved understanding of the neurocircuitry and neurochemistry underlying normal and deficient motivation, there is still no approved pharmacological treatment for such a deficiency. GPR139 is an orphan G protein-coupled receptor expressed in brain regions which contribute to the neural circuitry that controls motivation including effortful responding for reward, typically sweet gustatory reward. The GPR139 agonist TAK-041 is currently under development for treatment of negative symptoms in schizophrenia which include apathy. To date, however, there are no published preclinical data regarding its potential effect on reward motivation or deficiencies thereof. Here we report in vitro evidence confirming that TAK-041 increases intracellular Ca 2+ mobilization and has high selectivity for GPR139. In vivo, TAK-041 was brain penetrant and showed a favorable pharmacokinetic profile. It was without effect on extracellular dopamine concentration in the nucleus accumbens. In addition, TAK-041 did not alter the effort exerted to obtain sweet gustatory reward in rats that were moderately food deprived. By contrast, TAK-041 increased the effort exerted to obtain sweet gustatory reward in mice that were only minimally food deprived; furthermore, this effect of TAK-041 occurred both in control mice and in mice in which deficient effortful responding was induced by chronic social stress. Overall, this study provides preclinical evidence in support of GPR139 agonism as a molecular target mechanism for treatment of apathy. Highlights: TAK-041 is a potent and selective agonist of GPR139. TAK-041 does not alter tonic dopamine release in the nucleus accumbens. TAK-041 increases responding for a gustatory reward in minimally food-deprived mice. TAK-041 does not increase responding for reward in moderately food-deprived rats. TAK-041 does not alter food intake.